2020
DOI: 10.1016/j.janxdis.2020.102248
|View full text |Cite
|
Sign up to set email alerts
|

Media use and acute psychological outcomes during COVID-19 outbreak in China

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

38
230
5
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(292 citation statements)
references
References 39 publications
38
230
5
19
Order By: Relevance
“…These beneficial effects of social media use on mental health contrast other recent studies reporting negative effects of use of Internet and social media on individuals' mental health during the COVID-19. 52 The enormous amount of distributed (dis)information on social media may disorient and overwhelm individuals. In addition, emotional COVID-19-related tweets 17 may amplify feelings of anxiety and depression, based on the contagious paradigm, defined as: ''the transfer of emotional states to others, leading them to experience the same emotions as those who share the same social network.''…”
Section: Discussionmentioning
confidence: 99%
“…These beneficial effects of social media use on mental health contrast other recent studies reporting negative effects of use of Internet and social media on individuals' mental health during the COVID-19. 52 The enormous amount of distributed (dis)information on social media may disorient and overwhelm individuals. In addition, emotional COVID-19-related tweets 17 may amplify feelings of anxiety and depression, based on the contagious paradigm, defined as: ''the transfer of emotional states to others, leading them to experience the same emotions as those who share the same social network.''…”
Section: Discussionmentioning
confidence: 99%
“…(30) Third, consistent with recent COVID-19 studies, exposure to pandemic-related media coverage was associated with greater pandemic-specific acute stress and depressive symptoms. (2,14) Daily hours of pandemic-related media exposure, increases in daily media use, and exposure to conflicting information in the news media all predicted acute stress and depressive symptoms. Indeed, frequency of exposure to conflicting information in news media was among the strongest predictors of pandemic-specific acute stress symptoms, suggesting the importance of providing consistent messaging to promote resilience and protect mental health when coping with an ambiguous collective stressor.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 at the initial outbreak constituted an uncontrollable and unpredictable stressor due to the high risk of contagion and the shortage of effective timely treatment and medical resources ( Xiao, Zhang, Kong, Li, & Yang, 2020 ). Furthermore, the obligation to quarantine ( Zhang et al, 2020 ), the media use related to the pandemic outbreak ( Chao, Xue, Liu, Yang, & Hall, 2020 ; Mertens, Gerritsen, Duijndam, Salemink, & Engelhard, 2020 ), the uncertainty and novelty of the virus ( Asmundson & Taylor, 2020 ) as well as the evidence of possible fatality ( Onder, Rezza, & Brusaferro, 2020 ), and the repeated exposure to media reports of increased casualty/infected cases ( Lima et al, 2020 ) might aggravate individuals' stress levels. Previous studies showed that exposure to uncontrollable or unpredictable disasters (e.g., earthquake, tsunamis, etc.)…”
Section: Discussionmentioning
confidence: 99%